Tindak Tutur Direktif Guru PAUD EBTA dalam Proses Belajar Mengajar Sebagai Pemerolehan Bahasa Anak 4 Tahun - Anita, Fenny; Suriadiman, Noprieka (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
A child's mastery of a language begins with the acquisition of the first language, which is often called the mother tongue. Apart from the mother tongue, which plays a role in children's language acquisition, the language of teachers at school also plays a role in the development of children's language acquisition and learning. In schools, language use is a reality of teacher-student communication interactions that take place in teaching and learning activities. The teacher's use of language with students in conversations in class, especially the teacher's speech, Speech acts are speech events because they involve parties speaking in certain situations and places. These two symptoms occur in one process, namely the communication process. The teacher's speech acts referred to in this research are directive speech acts. Directive speech acts have an important role in children's language acquisition because they are carried out by the speaker with the intention that the listener performs the action mentioned in the speech. This research aims to (1) describe the forms of directive speech acts used by teachers in the teaching and learning process in language acquisition for 4-year-old children at EBTA Paud and (2) describe teachers' directive speech strategies in the teaching and learning process at EBTA Paud. The data source in this research is the speeches of teachers who teach at EBTA Early Childhood Education. The data collection techniques used in this research are recording techniques and note-taking techniques. The results of the research found that the use of speech acts in the form of directive speech in the teaching and learning process by teachers at EBTA Early Childhood Education was orders, requests, or hopes, suggesting, advising, and challenging. There are two speaking strategies used by teachers in the teaching and learning process at Paud EBTA, namely the strategy of speaking frankly without preamble and the strategy of speaking frankly with positive politeness.